ANALISIS KINERJA KEUANGAN PADA KOPERASI UNIT DESA (KUD) MELATI DESA EMPAT BALAI KECAMATAN KUOK KABUPATEN KAMPAR - Nurhaliza "; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to analyze the financial performance of the Village Unit Cooperative (KUD) Melati Desa Empat Balai, Kuok Subdistrict, Kampar Regency from 2016 to 2020. Based on the Liquidity Ratio, Solvency and Profitability. The research was conducted at the Village Unit Cooperative (KUD) Melati Desa Empat Balai Kecamatan Kuok Kampar Regency with the method used in the form of a quantitative descriptive method is a method that is expressed in the form of words, sentences, and numbers. The data used is the Melati KUD Balance Sheet in 2016-2020 and the Business Result Calculation report (PHU). The data collection technique used is the interview and documentation method. The data analysis technique used is to collect and classify financial statement data and to conduct an assessment of financial performance. Based on the results of the financial data analysis of the Melati Village Unit Cooperative (KUD) of Empat Balai Village, Kuok District, Kampar Regency, it was concluded that: (1) Current Ratio in 2016-2020 was with an average good criteria. (2) Cash Ratio for with an average poor criteria. (3) Debt to Asset Ratio (DAR) in 2016-2020 is with very good criteria . (4) Debt to Equity Ratio (DER) in 2016-2020 is with an average very good criteria. (5) Net Profit Margin (NPM) for 2016-2020 is with an average very good criteria. (6) Return on Assets (ROA) in 2016-2020 is with an average poor criteria . And (7) Return On Equity (ROE) in 2016-2020 with an average poor criteria . Keywords: Liquidity, Solvency, and Profitability